THE IMPLEMENTATION OF HIGHER EDUCATION STRATEGIC MANAGEMENT DURING THE COVID-19 PANDEMIC AT YOGYAKARTA STATE UNIVERSITY - Fitriana, Kurnia Nur; Anggalini, Titis Dewi; Satlita, Lena; Damayanti, Arista; Saputra, Irfan Adi (Natapraja, 2021)
The Covid-19 pandemic has a high impact on higher education governance so that it has the potential to reduce the performance of the institution. Universities must adapt and innovate in strategic management to respond to environmental changes during the Covid-19 pandemic. This study aims to explain the results of the implementation of strategic management carried out by Yogyakarta State University (YSU) during the Covid-19 pandemic. Data collection is done through documentation from journals, books, YSU performance reports, Kemendikbud performance reports, policy documents, documentation of mass media reports. The data needed is in the form of secondary data that can support (4) generating strategies to be implemented in higher education management during the Covid-19 pandemic, (5) formulating policy recommendations. The analysis was carried out by collecting data, reducing data, submitting data, as well as verifying and drawing conclusions. The achievements of the implementation of the strategic management of universities during the COVID-19 pandemic with the YSU case study showed stagnation in the fields of education services, student affairs, human resource development, research and service. Implementation of agile organization and adaptive governance in higher education governance can be done with the following principles 6 principles.